Factors Affecting Treatment Compliance of Patients With COPD During the COVID-19 Pandemic - Doğru, Sibel; Fakılı, Füsun; Aytaç, Sema; Sezgi, Cengizhan; Taylan, Mahşuk; Bayram, Nazan Gülhan; Uyar, Meral (European Journal of Therapeutics, 2023)
Objective: This study aimed to investigate the effects of difficulties experienced in the follow-up and treatment during the Coronavirus 2019 pandemic (COVID-19p), which included COVID-19 phobia and depression, on treatment compliance in patients with Chronic Obstructive Pulmonary Disease (COPD). Methods: This study included 123 patients with COPD. The COVID-19 Phobia Scale (C19P-S), Beck Depression Inventory (BDI), and Medication Adherence Report Scale (MARS) were used to assess the patients. Results: The mean age of patients with COPD was 64.56 ± 9.31 years. It was determined that our patients did not maintain regular outpatient follow-up mostly because of the fear of COVID-19 transmission (78.8%). Overall, 24% of our patients showed treatment noncompliance. A statistically significant relationship was found between COPD stages B and D and treatment compliance (p=0.01). Patients with frequent emergency department admissions (p = 0.01) and those with high BDI (p = 0.01) and C19P-S (p = 0.02) scores during the pandemic were found to have reduced treatment compliance. Conclusion: Patients with COPD with COVID-19 phobia, and depression had reduced treatment compliance. İt is necessary to be aware of these conditions and to plan appropriate interventions.